(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The efficient design and analysis of Steel Composite I-Girder bridges are critical for modern infrastructure, offering both economic and structural advantages. This study investigates the application of Midas Civil software in the analysis and design of these bridges, focusing on its capabilities to handle complex geometries, load conditions, and composite behavior. Midas Civil, a sophisticated structural analysis tool, provides an integrated platform for modeling, simulation, and optimization, making it well-suited for evaluating the performance of composite I-girder bridges under various scenarios. The present study is based on analysis and design of Composite Single Span Steel Composite-I Girder Bridge under IRC loadings using MIDAS CIVIL Software. The analysis was conducted to obtain various results such as bending moment, shear force, stresses, displacement and time-dependent characteristics like creep and shrinkage. The moving load consideration is as per IRC:6-2017 and compressive strength are defined as per IRC 112:2011.